Analysis of current-voltage characteristics of Al/p-ZnGa2Se4/n-Si nanocrystalline heterojunction diode - Yahia, I. S.; Fadel, M.; Sakr, G. B.; Yakuphanoğlu, Fahrettin; Shenouda, S. S.; Farooq, W. A. (Elsevier Science Sa, 2011)
The polycrystalline ZnGa2Se4 thin film was prepared by thermal evaporation technique on n-Si wafer followed by annealing at 700 K. Then, the Al/p- ZnGa2Se4/n-Si/Al heterojunction diode was fabricated. XRD pattern shows that the annealed ZnGa2Se4 film has a polycrystalline structure. AFM images indicate that the ZnGa2Se4 film is formed of nanoparticles. The dark current-voltage characteristics of the heterojunction diode at various temperatures have been investigated to determine the electrical parameters and conduction mechanism. The Al/p-ZnGa2Se4/n-Si/Al diode shows a rectification ratio of 2.644 x 10(2) at +/- 2 V at room temperature. It was found that at forward bias voltages <= 0.5 V, the conduction mechanism of the diode is controlled by the thermionic emission mechanism, while at bias voltages higher than 0.5 V. it is controlled by the space charge limited current mechanism. The series resistance R-s, the ideality factor n and the barrier height phi(b) values of the diode are determined by performing different plots from the forward current-voltage characteristics. The reverse current mechanism of the diode is controlled by the carrier generation-recombination process in the depletion region. The obtained results show that the Al/p-ZnGa2Se4/n-Si/Al heterojunction is a good candidate for the electronic device applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ZnGa2Se4 defect chalcopyrite; Thin film; XRD and AFM; Nanostructure heterojunction diode; Current-voltage characteristics